Kenya : Public Expenditure Review 2004, Report on the Structure and Management of Public Spending - World Bank (Washington, DC, 2012)
This Public Expenditure Review (PER) report carries an ex-post evaluation of a) budget performance in 2002/03 and, where information is available, for 2003/04 against fiscal objectives and spending priorities as set in the Economic Recovery Strategy for Wealth and Employment Creation (ERS); and, b) the Performance of budgetary institutions in the context of the government's public expenditure management (PEM) reform program. It also pulls together main features of spending patterns, and policy issues in key line ministries from the ministerial public expenditure reviews. In each of these areas, the report makes recommendations for further reform. The report also draws upon the findings of the Public Expenditure Management Assessment Action Plan (PEM-AAP) update, and the medium term expenditure framework (MTEF) Review. In an update carried out in 2004, PEM systems were found to meet 4 of the 16 benchmarks, which indicate that a much more concerted effort is needed to improve PEM in Kenya. There are two key indicators of weak PEM in Kenya: a big gap between the original (printed) budget and outturn, and, a huge stock of expenditure arrears. There are notable weaknesses in PEM that must be resolved before the budget can be wielded as an effective instrument for strategic linking of resources and spending. Within the MTEF process, key issues point at: the MTEF and annual budgeting remain two separate processes; the Planning-Finance split between the MTEF process and the annual budget is not conducive to effective integration of spending priorities and resource allocation; there is no single budget strategy document that could provide a reasonably firm reconciliation of resources and priorities; there is lack of political engagement in budget strategy and sector ceilings determination; and, the budget formulation timetable is too compressed. Key recommendations of the PER suggest developing and implementing a credible Medium-Term Fiscal Strategy; prioritizing expenditure to achieve the economic recovery strategy (ERS) Objectives; and, strengthening PEM.